2021
DOI: 10.48550/arxiv.2105.10646
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Entanglement dynamics for two-level quantum systems coupled with massive scalar fields

Yuebing Zhou,
Jiawei Hu,
Hongwei Yu

Abstract: Entanglement is essential in quantum information science. Typically, the inevitable coupling between quantum systems and environment inhibits entanglement from being created between long-distance subsystems and being maintained for a long time. In this paper, we show that when the environment is composed of a bath of massive scalar fields, the region of the separation within which entanglement can be generated is significantly enlarged, and the decay rate of entanglement is significantly slowed down compared w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 43 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…( 12) and ( 13), one finds that, for uniformly accelerated Unruh-DeWitt detectors in the Minkowski vacuum, Ω a is not only related to the field mass m/ω, but also to the acceleration a/ω. However, for the static ones in a thermal bath, Ω β is only related to m/ω but not to the temperature of the bath T U [41]. This leads to significant differences between the two cases.…”
Section: The Acceleration Effectsmentioning
confidence: 97%
See 4 more Smart Citations
“…( 12) and ( 13), one finds that, for uniformly accelerated Unruh-DeWitt detectors in the Minkowski vacuum, Ω a is not only related to the field mass m/ω, but also to the acceleration a/ω. However, for the static ones in a thermal bath, Ω β is only related to m/ω but not to the temperature of the bath T U [41]. This leads to significant differences between the two cases.…”
Section: The Acceleration Effectsmentioning
confidence: 97%
“…6 and 7, it is shown that, compared with the massless case, the region of separation ωL within which entanglement can be created is expanded when the acceleration a/ω is smaller than a critical value a crit /ω determined by the field mass m/ω, and is compressed when a > a crit . This is distinct from the fact that the region of separation for entanglement generation is always expanded for a static quantum system coupled with massive fields (in vacuum or in a thermal bath), compared with the massless case [41].…”
Section: The Mass Effectsmentioning
confidence: 98%
See 3 more Smart Citations